LandScriptDeforestMap : an R package to evaluate deforestation in remote sensing images - Gomes, Thiago Lappicy Lemos (2024)
The LandScriptDeforestMap R package was developed for mapping and measuring deforestation dynamics using classified satellite images. It can be applied to different land cover types and grid sizes and was widely tested throughout the Amazon. This package allows providing information to different stakeholders focused on assessing and detecting deforestation and identifying possible driving causes (e.g. agriculture, pasture, urban growth, mining). This tool is of great value when designing new public policies dedicated to the sustainable management of land/forest, and contributes to the Sustainable Development Goal 15, aiding in a more transparent discussion and focusing on public policies driven by data.